A Study of Sacral Index and Its Interpretation in Sex Determination in Madhya Pradesh - Patel, Shailendra; Nigam, Manish; Mishra, Pradeep; Waghmare , Chandra Shekhar (Journal of Indian Academy of Forensic Medicine, 2014)
Various parameters and indices are available based on which the sex can be determined using sacrum. These parameters and indices vary region wise also. Therefore we undertook the study in Madhya Pradesh region. Total 126 dry human adult sacra of known sex (76 male & 50 female) were obtained from various Medical Colleges of Madhya Pradesh. Maximum length and maximum width of sacrum were studied. Sacral index (SI) arrived from the measured parameters. Demarking Point (DP) helps in sexing the sacrum with certainty. Maximum length of sacrum is found statistically significant (p-<0.0001, t=8.67), DP for maximum length for male sacrum is >124.40 mm and for female is <81.92 mm. Maximum width of sacrum is found statistically not significant (p=0.99, t=0.018). The SI is found statistically significant (p- <0.0001, t=9.63) for sexing the sacrum in the present study. DP of SI for male is <84.20 and for female is > 123.06 and 6.57% male and 12% female sacra fall beyond DP.